2021
DOI: 10.3390/antibiotics10070853
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of the Involvement of Clinical Pharmacists in Antimicrobial Stewardship Programs on the Incidence of Antimicrobial-Related Adverse Events in Hospitalized Patients: A Multicenter Retrospective Study

Abstract: Although specialized pharmacists have been suggested to be essential members of antimicrobial stewardship programs (ASPs), not all hospitals in Korea operate ASPs with pharmacists involved. We aimed to evaluate the association of involvement of clinical pharmacists as team members of multidisciplinary ASPs with the incidence of antimicrobial-related adverse drug events (ADEs). Five tertiary teaching hospitals participated in this retrospective cohort study. At each participating hospital, we randomly selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…38 Another retrospective study in South Korea reported that an ASP with clinical pharmacist involvement was associated with a decrease in the incidence of antimicrobialrelated adverse events (8.9% vs 14.7%; P < .001). 39 Finally, similar to previous studies, a study on clinical pharmacist involvement in the ASP in India showed an increase in the proportion of appropriate prescriptions during the third year of the intervention period. 40 Similar to those reported in Western developed countries like the United States, the acceptance rates of clinical pharmacist recommendations in Asia range from 70% to 94%.…”
Section: Evidence On the Efficacy Of Pharmacist-driven Asps In Asiasupporting
confidence: 81%
“…38 Another retrospective study in South Korea reported that an ASP with clinical pharmacist involvement was associated with a decrease in the incidence of antimicrobialrelated adverse events (8.9% vs 14.7%; P < .001). 39 Finally, similar to previous studies, a study on clinical pharmacist involvement in the ASP in India showed an increase in the proportion of appropriate prescriptions during the third year of the intervention period. 40 Similar to those reported in Western developed countries like the United States, the acceptance rates of clinical pharmacist recommendations in Asia range from 70% to 94%.…”
Section: Evidence On the Efficacy Of Pharmacist-driven Asps In Asiasupporting
confidence: 81%
“…A multidisciplinary antimicrobial stewardship approach, active involvement of a drug and therapy committee or equivalent, formulary limitations, and the availability of antimicrobial stewardship education and training for pharmacists and physicians are essential components for an antimicrobial stewardship program to be considered successful in Makkah region hospitals [26]. The potential for pharmacist involvement in Antimicrobial stewardship program in the incidence of Adverse drug events shows a much lower proportion of Adverse events than in other hospitals that do not involve a pharmacist.These results suggest that the active involvement of pharmacists in multidisciplinary Antimicrobial stewardship program contributes to reducing the incidence of antimicrobial adverse drug events in hospitalized patients [27]. Pharmacist-led ASP was associated with a reduction in the number of days of antimicrobial therapy for uncomplicated gram-negative bacteremia among patients admitted to a community hospital without an infectious disease specialist.…”
Section: The Role Of Pharmacists In Antimicrobial Stewardship Programsmentioning
confidence: 77%
“…In Korea, a multicenter study was conducted in five general hospitals to investigate the incidence of adverse reactions to antimicrobial agents. Hospitals that implemented multidisciplinary ASPs that included pharmacists had a lower incidence of adverse reactions to antimicrobial agents than those with ASPs without pharmacists (8.9% vs. 14.7%, P <0.001), and ASPs managed by a multidisciplinary teams that included pharmacists had a 38% lower incidence of adverse reactions to antimicrobial agents (OR: 0.62) [ 170 ].…”
Section: Recommended Guidelines For Each Key Questionmentioning
confidence: 99%